Pengukuran Nilai Perusahaan: Berdasarkan Struktur Kapital, Kebijakan Dividen, Pertumbuhan Perusahaan, dan Profitabilitas - Ashilla Safaniza Darmawan; Shinta Permata Sari (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
Company value is a key indicator that shows the success of management in managing resources and creating profits for shareholders. This study aims to analyse the effect of capital structure, dividend policy, company growth, and profitability on company value in the Basic Materials sector listed on the Indonesia Stock Exchange (IDX) for the period 2022-2024. The research method used is quantitative with a multiple linear regression approach. The data used is secondary data in the form of annual financial reports obtained from the IDX website. The research sample was determined using purposive sampling technique, resulting in 30 companies with 90 data observations. The results show that capital structure and dividend policy do not affect company value. This indicates that debt levels and dividend distribution policies are not yet major factors considered by investors in assessing companies. Company growth has a negative effect on company value, which means that an increase in assets is not fully accompanied by an increase in performance. Meanwhile, profitability has a positive effect, indicating that a company's ability to generate profits is a major factor in increasing company value.